Correlation between gallstones and fasting blood glucose to serum high-density lipoprotein cholesterol ratio among American adults - Wu, Bo; Zheng, Huachao; Zhuang, Caixiang; Mao, Jiesheng; Yuncheng, Luo; Huang, Lidong; Li, Min; Feiyang, Zhao; Lin, Sisi; Wang, Pengwei; Hu, Yiren (Frontiers in Medicine, 2025)
BackgroundResearch indicates that the ratio of fasting blood glucose (FBG) to serum high-density lipoprotein cholesterol (HDL-C) (GHR) can accurately predict many diseases. Nevertheless, the relationship between GHR and the risk of gallbladder stones remains unclear. This study investigates the possible relationship between GHR and the incidence of gallbladder stones.MethodsThis research used information gathered from the National Health and Nutrition Examination Survey (NHANES) between March 2017 and March 2020. A calculation was made to determine the GHR by dividing the fasting blood glucose level by the HDL-C level. Several statistical methods, including analysis of threshold effects, smoothed curve fitting, multiple logistic regression modeling, and subgroup analysis, were utilized to investigate the connection between GHR and gallstones.ResultsIn 3898 U.S. adults, GHR was significantly positively associated with the prevalence of gallbladder stones. In a fully adjusted model, the incidence of gallbladder stones increased by 7% with each 1-unit increase in GHR (OR [95% Cl] = 1.07 [1.02, 1.14]). Compared with members in the low group, those in the high group had a 100% higher likelihood of getting gallbladder stones (OR [95% CI] = 2.00 [1.31, 3.04]), and this stabilizing connection was always present in the different subgroups. With the help of smooth curve fitting, the research also showed that there was a connection that was formed like an upside-down L shape between GHR and gallbladder stones. The analysis of the threshold effect revealed that the inflection point was 4.28.ConclusionThe results revealed an inverted L-shaped connection between GHR and gallbladder stones. Keeping GHR levels within a certain range is associated with a lower incidence of gallstones in the general population.